Jimmy Carter [videorecording (DVD)] - Bosch, Adriana; Hunt, Linda; Carter, Jimmy, 1924- (PBS Home Video, 2008)
Examines the failings of Carter's political leadership in the context of the turbulent 1970's ; and explores the role religion played in his career.